Engagement, involvement and empowerment: Three realms of a coproduction framework for climate services. (May 2021) - Bojovic, Dragana; St. Clair, Asuncion Lera; Christel, Isadora; Terrado, Marta; Stanzel, Philipp; Gonzalez, Paula; Palin, Erika J.
Graphical abstract: Highlights: Climate services coproduction should result in transdisciplinary knowledge production. Our coproduction framework goes from awareness raising to co-development. Participatory processes gradually involve more specialised stake(&knowledge)holders. Scientists become co-learners and empower users to contribute to shared knowledge. Successful coproduction integrates both the process and the end product or service. Abstract: While knowledge coproduction between climate scientists and climate information users has become a common theme in the climate services discourse, the interface between climate service providers and users is an aspect of climate services projects that still calls for more attention. This is due in part to the dominance of the physical sciences in these projects, as well as the prevalence of an instrumental and narrow interpretation of coproduction. Following up on the World Meteorological Organisation's Guidance on Good Practices for Climate Services User Engagement, and incorporating insights from the social and human sciences, we develop a coproduction framework for climate services to help establish a smooth and effective interface between scientists and stakeholders. This framework is intended for research and innovation projects developing climate knowledge and services. The coproduction framework comprises three realms: (i) engagement using various communication channels; (ii) involvement through interviews, workshops and webinars; and (iii) empowerment of stakeholders and scientists through focused relationships. This incremental participatory process involves stakeholders in increasingly profound ways: from a broad stakeholder group identified through awareness-raising campaigns, on to potential users with whom we exchange knowledge, and then to a set of "champion users" who co-develop the service and pioneer its use in decision-making processes. This paper illustrates the application of the coproduction framework in PRIMAVERA, an EU H2020-funded project for designing, running and testing new high-resolution global climate models and evaluating their outputs. While PRIMAVERA provided ground breaking scientific findings that could potentially benefit various stakeholders and support climate risk assessment activities, these results are highly specialised and their added value has yet to be assessed. Accordingly, the user engagement component of the project faced the challenging task of both motivating stakeholders' participation in the project and motivating future users of potential services based on PRIMAVERA data. The trial of the framework in PRIMAVERA provided key lessons for enhancing coproduction in research and innovation projects. We demonstrate how the role of scientists gradually shifted in this coproduction cycle from masters of knowledge(Roux et al., 2017) to co-learners, and how the involvement of the project's interdisciplinary team and their interaction with stakeholders served to move the project towards transdisciplinary knowledge production.